Learning technology : a handbook for FE teachers and assessors - Scott, Daniel (Further education, 2018)
References and further reading; Chapter 3 Deliver and facilitate; Introduction; Safe practice of ILT; False information; Enabling successful delivery with ILT; Basic technical solutions; Display, Engage, Participation model; The LearningWheel; Learning spaces; ILT in employability; eTutoring; Designing online activities; Accessibility and assistive technologies; Summary; References and further reading; Chapter 4 Assess; Introduction; eAssessment; Designing for eAssessment; Assessment planning; Assessment activity; Giving feedback; Collecting work-based evidence; ePortfolios